Community Empowerment Through Social-Culture to Enhance Human Resources - Septiana, Riska; Ummah, Qorinatul; Muslim, Rachmat Imam; Wuryani, Meilan Tri (Universitas Muhammadiyah Surakarta, 2023)
As for the choice of the Karangmalang Wetan village, Kangkung Sub-District, Kendal Regency as the subject of community empowerment through social culture because the college conducting Community Service Program in Karangmalang Wetan Village found obstacles in implementing the prospects for social institutions and a lack of quality human resources throughout the village so that it requires more habituation of activities effectively through the implementation of several work program Community Service Program. This research uses the implementation method of community empowerment through the socio-cultural field. The results of the implementation of the Community Service Program work program in the socio-cultural field are that all residents can strengthen their relationships with people so that they are more harmonious and establish good friendships, residents have a realization of the importance of cooperation and care for others, residents can care about learning and maintaining culture native village, residents are also conscious of the importance of saving the environment clean to create a healthy and comfortable environment.